A Comparative Study of Different Load Balancing Techniques - Parashar, Jyoti; Avinash Sharma, Dr. (International Journal of Engineering and Technology, 2018)
Cloud computing is a new technology used to manipulate, configure and can be used to access distributed computing applications in the network. It implements the load balancing approach which is used to distribute all of its workload to every node connected in the network. By using this technique resource utilization is done properly. It can also used to achieve user satisfaction and computing resources. If load balancing is used properly then it can efficiently and properly implement the fail-over, scalability, over- provisioning techniques. It can also minimize the resources used and avoid the bottleneck. In my research, review of different load balancing techniques, its usage, limitations, applications and various performance metrics are described..Â Â